Descriptive of Coronary Vessel Lesions Number in DM and non-DM Patients Based on CAG - Edwin Setiabudi; Dimas P Baskara (Journal of Medicine and Health, 2022)
Diabetes Mellitus (DM) is a chronic hyperglycemia condition caused by inadequate insulin secretion or due to failure of insulin response, which is a risk factor for coronary heart disease (Coronary Artery Disease, CAD). CAD is caused by plaque buildup on the walls of the arteries that supply blood to the heart (called coronary arteries) and other parts of the body. The aim of this study was to compare the severity of coronary lesions in DM and non-DM patients who were equipped with CAD. Descriptive research design using 229 experimental subjects, the subjects involved were based on predetermined inclusion and exclusion criteria. The results showed that the DM group experienced more Triple Vessel Disease (TVD) (47.83% vs. 35.92%) than the non-DM group, however, the number of Single Vessel Disease (SVD) was smaller (17.38% vs. 26.70%). The conclusion from this study is that DM patients have a higher coronary lesion severity than non-DM patients as evidenced by the number of triple vessel disease (TVD) on examination by coronary angiographic. Keywords: coronary artery disease, coronary angiographic, diabetes mellitus, non-diabetes mellitus, triple vessel disease